Atomistic congestion tolls at concentrated airports?: seeking a unified view in the internalization debate - Jan Keith Brueckner; Kurt van Dender (Center for Economic Studies and ifo Institute (CESifo), 2007)
The goal of this paper is to bring some unity to the theoretical side of the debate on internalization of airport congestion by showing that all the literature's theoretical results can be derived within one simple and unified framework. The analysis starts by replicating the results of Brueckner (2002), who showed that, because airlines behaving in Cournot fashion internalize congestion, they should be charged low congestion tolls. The analysis then validates the findings of Daniel (1995), who argued that larger atomistic tolls are required in a model where a Stackelberg leader interacts with competitive fringe airlines. However, it is shown that this result only holds approximately when the carriers' outputs are imperfect substitutes.
Keywords: H23; L50; L9; 330; Flughafen; Luftverkehr; Verkehrsstau; Straßenbenutzungsgebühr; Bottleneck; Internalisierung externer Effekte; Theorie